2014 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining (ASONAM 2014) 2014
DOI: 10.1109/asonam.2014.6921608
|View full text |Cite
|
Sign up to set email alerts
|

Empirical study on overlapping community detection in question and answer sites

Abstract: In many social networks, people interact based on their interests. Community detection algorithms are then useful to reveal the sub-structures of a network and help us find interest groups. Identifying these social communities can bring benefit to understanding and predicting users behaviors. However, for some kind of online community sites such as question-and-answer (Q&A) sites or forums, there is no friendship based social network structure, which means people are not aware who they are in contact with. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
2
0
4
Order By: Relevance
“…They found that NB classifier has an overall success rate of 84.16 and 92.5 percent on How-to-do-it questions category. Similarly, Meng, Gandon, Faron-Zucker and Song (2015), Meng, Gandon and Zucker (2015), Meng, Gandon, Zucker and Song (2014) suggested a proficient approach for collecting topics from Q&A to identify the communities of interest. They thoroughly compared and applied three detection methods: graph based, clustering based, and LDA based on SO.…”
Section: Mining So For Software Developmentmentioning
confidence: 99%
“…They found that NB classifier has an overall success rate of 84.16 and 92.5 percent on How-to-do-it questions category. Similarly, Meng, Gandon, Faron-Zucker and Song (2015), Meng, Gandon and Zucker (2015), Meng, Gandon, Zucker and Song (2014) suggested a proficient approach for collecting topics from Q&A to identify the communities of interest. They thoroughly compared and applied three detection methods: graph based, clustering based, and LDA based on SO.…”
Section: Mining So For Software Developmentmentioning
confidence: 99%
“…A identificac ¸ão destes grupos pode ser alcanc ¸ada através de métodos de detecc ¸ão de comunidades. Para isso existem 3 principais tipos de abordagem [Meng et al 2014]: métodos baseados em grafos, métodos de agrupamento e métodos baseados em modelos. A primeira consiste em inferir um grafo através das interac ¸ões no fórum e, posteriormente, utiliza-se algum método de detecc ¸ão de comunidades em redes [Xie et al 2013][Cuijuan Wang andWang 2015] no grafo inferido.…”
Section: Grupos De Colaborac ¸ãO No Stackoverflowunclassified
“…Outra forma de abordar este problema é através da utilizac ¸ão de métodos de agrupamento. Neste caso, calcula-se a similaridade dos perfis dos usuários e utiliza-se métodos de agrupamento baseados em similaridade [Meng et al 2014]. Nesta abordagem a estrutura da rede não é considerada e cada usuário é atribuído a apenas um grupo.…”
Section: Grupos De Colaborac ¸ãO No Stackoverflowunclassified
See 1 more Smart Citation
“…Thus previous community-detection algorithms cannot apply on these social webs because they have no explicit friendship networks. There are three kinds of approaches for community detection in these networks [21], depending on their input: a graph-based approach; a clustering-based approach; and a model-based approach. The first one extracts an implicit network structure from interaction traces in order to overcome the traditional community-detection problem.…”
Section: Background and Related Workmentioning
confidence: 99%